Plagiarism Detection Techniques for Arabic Script Languages: A Literature Review - Ibrahim, Ribwar; Saeed, Soran; Wakil, Karzan (Kurdistan Journal of Applied Research, 2017)
Plagiarism is generally defined as literary theft and academic dishonesty. This considered as the serious issue in an academic documents and texts. There are numerous of plagiarism detection techniques have been developed for various natural languages, mainly English. In this paper we investigate and review the plagiarism detection techniques and algorithms which have been developed for Arabic Script Languages (ASL), and providing a literature review of the utilized methods in terms of techniques and outcomes. The result of this paper will help the researchers who are going to commence their development and extend their researches in ASL like Arabic, Persian, Urdu, and Kurdish.